2013
DOI: 10.5194/angeo-31-2097-2013
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of a NTC radio source from a Cluster tilted spacecraft pair

Abstract: Abstract. The Cluster mission operated a "tilt campaign" during the month of May 2008. Two of the four identical Cluster spacecraft were placed at a close distance (∼ 50 km) from each other and the spin axis of one of the spacecraft pair was tilted by an angle of ∼ 46 • . This gave the opportunity, for the first time in space, to measure global characteristics of AC electric field, at the sensitivity available with long boom (88 m) antennas, simultaneously from the specific configuration of the tilted pair of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Such maps have been used in Grimald at al. (2008) and in Décréau et al (2013). We take the opportunity of this new analysis of NTC events previously published to correct an error which appears in the maps published in the two papers quoted above.…”
Section: P M E Décréau Et Al: Wide-banded Ntc Radiation 1287mentioning
confidence: 89%
See 2 more Smart Citations
“…Such maps have been used in Grimald at al. (2008) and in Décréau et al (2013). We take the opportunity of this new analysis of NTC events previously published to correct an error which appears in the maps published in the two papers quoted above.…”
Section: P M E Décréau Et Al: Wide-banded Ntc Radiation 1287mentioning
confidence: 89%
“…8 and 9). Note that the resulting orientations are only a crude indication of correct values, since the underlying assumption (circular polarization of electric field) is likely not fully satisfied (see Décréau et al (2013) for an estimation of possible errors), and that measurement uncertainties are large. Nevertheless, Fig.…”
Section: Position Of Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…On 3 April 1997, the SPC approved the Cluster II mission to be launched in 2000 on two Soyuz rockets (Credland and Schmidt, 1997). In a little more than 3 years, the fastest implementation time for an ESA space mission, the four Cluster spacecraft were rebuilt, tested and successfully launched on 16 July and 9 August 2000 (Escoubet et al, 2001). …”
Section: Mission Selection and Launchmentioning
confidence: 99%
“…2). Décréau et al (2013) showed that classical triangulation, in this case using three of the non-tilted spacecraft situated thousands of kilometres apart, can lead to a source location that is nowhere near the boundaries where NTC generation occurs. The erroneous source location, far from these boundaries, given by triangulation is attributed to small deviation from the assumed polarisation of the emission.…”
Section: Plasmasphere and Ring Currentmentioning
confidence: 99%